혈관평활근세포에서 고농도 포도당이 유도한 TSP-1 발현과 MMP-2 활성에 미치는 Epicatechin의 효과 - 류경렬; Gyeong Ryul Ryu; 강정훈; Jung Hoon Kang; 홍경자; Kyong Ja Hong; 정인경; In Kyung Jeong; 장화인; Hwa In Jang; 이덕주; Duck Joo Rhie; et al. (Endocrinology and metabolism (Seoul), 2006)
연구배경: 혈당이 조절되지 않는 당뇨병 환자에서 혈장내의 고혈당은 동맥경화증과 같은 혈관계 합병증을 유발한다. 특히, 고혈당은 혈관평활근세포에서 thrombospondin-1 (TSP-1)의 분비를 촉진하며, matrix metalloproteinase-2 (MMP-2)를 활성화시켜 혈관평활근세포의 이주를 촉진한다. 한편 항산화 및 항암효과가 보고된 catechin 계열이 MMP-2 활성을 억제한다는 연구 결과가 최근 보고되었다. 따라서 본 연구는 catechin 계열에 속하는 epicatechin이 고농도의 포도당에 노출된 혈관평활근세포에서 TSP-1 발현과 이주에 미치는 영향을 조사하였다. 방법: 혈관평활근세포는 Sprague-Dawley계 흰쥐 대동맥에서 분리하였다. 혈관평활근세포를 고농도의 포도당(30 mM)과 epicatechin (30, 100, 300 μM)에 노출시킨 후 TSP-1 단백질과 mRNA 발현을 Western blot과 Northern blot으로 관찰하였다. 역전사 중합효소연쇄반응을 이용하여 MMP-2 mRNA 발현을 관찰하였으며, MMP-2 활성과 혈관평활근세포의 이주능을 gelatin zymography와 Matrigel을 이용한 invasion assay로 각각 조사하였다. 결과: Epicatechin은 혈관평활근세포에서 고농도의 포도당이 유도한 TSP-1 발현과 MMP-2 활성을 농도의존적으로 감소시켰다. 또한 epicatechin은 고농도의 포도당에 의해 유도된 혈관평활근세포의 이주를 유의하게 감소시켰다. 결론: 이상으로 epicatechin은 고농도의 포도당이 유도한 TSP-1 발현과 MMP-2 활성을 억제하여 혈관평활근세포의 증식 및 이주를 차단하는 것으로 생각된다. 그러므로 epicatechin은 동맥경화증의 발생과 진행을 억제하는 역할을 하리라 생각된다. Background: The incidence of atherosclerosis is well correlated with the progression of type 2 diabetes mellitus. High plasma glucose in uncontrolled diabetic patients evokes many vascular complications such as atherosclerosis. Specifically, high glucose was reported to induce thrombospondin-1 (TSP-1), which activates matrix metalloproteinase-2 (MMP-2) and leads to the invasion of vascular smooth muscle cells (VSMCs) into the intima. Catechins with antioxidant effects are known to inhibit MMP-2 activity. Therefore, this study was aimed at revealing the effect of epicatechin, one of catechins, on high glucose-induced TSP-1 and the invasiveness of VSMCs. Methods: VSMCs were primarily isolated from Sprague-Dawley rat aorta. The VSMCs were incubated with different doses (30, 100 and 300 μM) of epicatechin under high glucose concentration (30 mM). The TSP-1 protein and mRNA expressions were analyzed by performing Western blotting and Northern blot analyses, respectively. RT-PCR was performed to observe the MMP-2 mRNA expression. Gelatin zymography was performed for the measurement of MMP-2 activity. Invasion assays were performed to evaluate the invasiveness of VSMCs. Results: Epicatechin inhibited the high glucose-induced TSP-1 expression and the MMP-2 activity in a dose-dependent manner. Also, epicatechin inhibited the high glucose-induced invasiveness of VSMCs across the matrix barrier in a dose-dependent fashion. Conclusion: Collectively, epicatechin may prevent the high glucose-induced proliferation and invasion of VSMCs by inhibiting the TSP-1 expression and the MMP-2 activity. Therefore, epicatechin appears to play a protective role in the development of atherosclerosis. (J Kor Soc Endocrinol 21:302~310, 2006)